Analisis Pengembangan Platform Digital dalam Strategi Pemasaran Produk Busana Syar’i Kenaya : Studi Kasus pada UMKM Arsy - Evi Suryani; Muhammad Sugiharto (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the marketing strategy implemented by UMKM Arsy in utilizing digital platforms to optimize market potential and increase product sales. This research uses qualitative methods. The respondents in this research are UMKM owners who adopt digital marketing, namely Arsy. Primary data is used in research using observation and interviews. The research was conducted in November 2024. The results of this research show that UMKM face challenges in understanding and implementing digital marketing effectively. The implication of this research is that ARSY requires learning and training from related parties to support the sustainability of this business.